The role of biotechnology for improvement of soybean production in sub-optimal land - Suyanto Pawiroharsono (Widyariset, 2012)
Soybean is the one of the most important food commodities after rice and maize. It is considered as significantprotein sources and is also used as raw material for several foods and feeds industries. The availabilityof soybean is mostly fulfilled from import, namely around 60% or 1.2 million ton/year. Therefore, the increaseof soybean productivity is an opportunity that should to be executed for minimizing the dependency of importedproduct. The development of soybean productivity for self supporting is very reasonable. The potencies, such as thetechnologies readiness (tolerant superior varieties and bio-fertilizer) and farming technology, are considered assuccess factors for supporting the increase of soybean productivities in sub-optimal lands. Meanwhile, the potencyof sub-optimal land for agriculture is still large quantity, namely 30.67 million hectares. The successful requiresthe supports of government policies and their commitments as well as the participation of farmer communities.